CICLO DE VIDA DE PELLIODITIS PELLIO (SCHNEIDER)(NEMATODA: RHABDITIDAE) PARASITO DE LARVAS DE SCAPTIA (SCAPTIA) LATA (GUERIN-MENEVILLE)(DIPTERA: TABANIDAE) - Camino, Nora B.; Stock, Patricia S. (Acta Entomológica Chilena, 2022)
Pellioditis pellio (Schneider)(Rhabditidae: Nematoda) was found for first time to Science, parasitizing tabanid larvae Scaptia (Scaptia) lata (Guerin-Meneville), in the lake sides of Puyehue lake in Osorno, Chile. The life cycle of this nematode was studied in Gallería mellonella larvae and also corroborated in its natural host.